**Use the quadratic formula**

\[

x=\frac{-b \pm \sqrt{b^2-4 a c}}{2 a}

\]

**Once in standard form, identify \(\mathrm{a}, \mathrm{b}\) and \(\mathrm{c}\) from the original equation and plug them into the quadratic formula.**

\[

\begin{aligned}

&x^2+2 x+1=0 \\

&a=1 \\

&b=2 \\

&c=1 \\

&x=\frac{-2 \pm \sqrt{2^2-4 \cdot 1 \cdot 1}}{2 \cdot 1}

\end{aligned}

\]

**Evaluate the exponent**

\[

\begin{aligned}

&x=\frac{-2 \pm \sqrt{2^2-4 \cdot 1 \cdot 1}}{2 \cdot 1} \\

&x=\frac{-2 \pm \sqrt{4-4 \cdot 1 \cdot 1}}{2 \cdot 1}

\end{aligned}

\]

**Multiply the numbers**

\[

\begin{aligned}

&x=\frac{-2 \pm \sqrt{4-4 \cdot 1 \cdot 1}}{2 \cdot 1} \\

&x=\frac{-2 \pm \sqrt{4-4}}{2 \cdot 1}

\end{aligned}

\]

**Subtract the numbers**

\[

\begin{aligned}

&x=\frac{-2 \pm \sqrt{4-4}}{2 \cdot 1} \\

&x=\frac{-2 \pm \sqrt{0}}{2 \cdot 1}

\end{aligned}

\]

**Evaluate the square root**

\[

\begin{aligned}

&x=\frac{-2 \pm \sqrt{0}}{2 \cdot 1} \\

&x=\frac{-2 \pm 0}{2 \cdot 1}

\end{aligned}

\]

**Add zero**

\[

\begin{aligned}

&x=\frac{-2 \pm 0}{2 \cdot 1} \\

&x=\frac{-2}{2 \cdot 1}

\end{aligned}

\]

**Multiply the numbers**

\[

\begin{aligned}

&x=\frac{-2}{2 \cdot 1} \\

&x=\frac{-2}{2}

\end{aligned}

\]

**Cancel terms that are in both the numerator and denominator**

\[

\begin{aligned}

&x=\frac{-2}{2} \\

&x=-1

\end{aligned}

\]